Indian Budget 2022: A Make-or-Break Moment for Cryptocurrency - Nanjundan, Preethi; James, Blesson Varghese; George, Jossy P; Kukreja, Dilpreet Kaur; Goyal, Yugjeet Singh (EAI Endorsed Transactions on Internet of Things, 2023)
People are liable to the tax rate if they transfer digital assets during a specific fiscal year. There is no distinction between income from businesses and investments or between short-term and long-term gains because the 30% tax rate is applicable regardless of the sort of income. By clearly stating how it would be charged, the Indian budget 2022 has provided some direction. Losses were consequently experienced by both new and old cryptocurrency buyers. Under Section 115 BBH, it is illegal to offset cryptocurrency losses with cryptocurrency gains—or any other gains or revenue, for that matter. The implementation of the 30% tax rule on digital assets has caused the collapse of the cryptocurrency market, and there is a possibility that investors will continue to suffer losses in the future.